A new strategy for the fabrication of high performance reactive microspheres via energetic polyelectrolyte assembly. Issue 2 (4th January 2017) - Zhang, Tianfu; Ma, Zhuang; Li, Guoping; Luo, Yunjun
Abstract : Al and Fe2 O3 NPs functionalized by GAP-based energetic polyelectrolytes assemble into reactive microspheres by electrostatic interaction. Abstract : Since the thermite reaction in aluminum-based nanostructured energetic materials (NEMs) is closely involved with Al and oxide nanoparticles (NPs), intimate interfacial contact between the Al and oxide NPs is widely considered to be a key parameter for the NEMs with high reactivity. With the aim to overcome the disadvantage of inert modifiers without energetic groups, used in the assembly approach, which is a cutting-edge solution to precisely organize the arrangement of the Al and oxide NPs and lead to enhanced intimacy, we successfully prepared GAP-based (GAP, glycidyl azide polymer) energetic polyelectrolytes (GEPEs) and demonstrated electrostatic assembly as a facile way to fabricate high performance, reactive Al/Fe2 O3 microspheres after modification of the Al and Fe2 O3 NPs with the GEPEs. The pressurization rate of the obtained reactive microspheres, a relative measurement of the reactivity, reached 410.36 MPa s −1, which is the highest value obtained so far, and is 1–2 orders of magnitude higher than that of other reported Al/Fe2 O3 NEMs. The incorporated GEPEs serve three main roles: GEPEs act as a modifier by interacting strongly with the NPs, and improve the intimacy of the Al and Fe2 O3 via powerful electrostatic attraction between the modified NPs; the assembly of the reactive microspheres can be achieved through the directing assembly of the GEPEs themselves; internal gas released by the decomposition of energetic sites existing inside the assembled microspheres rapidly separates the NPs to prevent adverse sintering and to weaken the nanostructure loss during the reaction, resulting in an improvement of the reactivity.